Pemodelan Indeks Pembangunan Kesehatan Masyarakat Kabupaten/Kota di Pulau Kalimantan Menggunakan Pendekatan Regresi Probit - M. Fathurahman (Universitas Bumigora, 2019)
The Public Health Development Index (PHDI) is a composite indicator that describes the progress of health development and is useful for ranking provinces and districts/cities in achieving successful community health development. In addition, the PHDIM can also be used to determine regional priorities that require assistance in improving health development. Based on the publication of the PHDI ranking by the Health Research and Development Agency of the Ministry of Health in 2013, the PHDI ranking for 55 districts/cities in Kalimantan Island varied greatly. So it needs to be studied, examined the factors that influence it. The purpose of this study was to examine the modeling of the factors that influence the PHDI of districts/cities in Kalimantan Island in 2013 using the probit regression approach. The results of this study indicate that the factors that significantly influence the PHDI of districts/cities in Kalimantan Island in 2013 are the human development index and the labor force participation rate.